Spatial dynamic simulation of beetles in biodiversity hotspots - He, Ping; Bai, Ming; Li, Lulu; Lu, Yuanyuan; Li, Jing; Yan, Zihan (Frontiers in Ecology and Evolution, 2024)
Introduction Coleoptera is the most species-rich order of animals with the widest distribution area; however, little is known about its global suitability distribution, and a substantial number of species are experiencing silent extinction. Most of Earth’s biocommunities are concentrated in biodiversity hotspots, and these hotspots receive the largest investment of conservation funds. The survival of beetles is closely related to the richness of biodiversity, so habitat loss in hotspots results in a high extinction risk for beetles. Methods We used the MaxEnt model to simulate the spatial suitable distribution in six time periods (1970-1980, 1980-1990, 1990-2000, 2000-2010, 2010-2020, and 1970-2020). Furthermore, we determined the priority suitable regions in hotspots after coupling the current biodiversity zones and evaluated the congruence between the suitable habitat of beetles and hotspots. Results The results revealed that less than 30% of suitable regions were located in hotspots, and approximately 49.08% of the suitable habitat remained constant in all six periods, and can be regarded as climatically stable refugia. The Mediterranean Basin had the largest suitable area in each period and was always ranked first; other regions, such as Indo-Burma, Irano-Anatolian, and Mesoamerica, also had large areas of suitable habitat. Nine excellent, ten stable, and seventeen lower hotspots were identified based on their dynamic changes in 36 hotspots. Discussion Based on these results, corresponding planning and management measures should be implemented in different biodiversity hotspots according to the changes in geographic distribution. In this paper, we propose practical advice for different regions to improve isolated and fragmented habitats, which will support the conservation of Coleoptera taxa and the restoration of biodiversity.